Dual-wideband bandpass filter with independently controllable center frequencies and wide stopband. Issue 1 (20th November 2017) - Xiong, Yang; Wang, Litian; Pang, Doudou; Zhang, Wei; Zhang, Fan; He, Ming; Zhao, Xinjie; Zhang, Xu
Abstract : In this paper, a dual-wideband bandpass filter (BPF) with independently controllable center frequencies (CFs) and wide stopband suppression is presented using a new quintuple-mode resonator (QMR). By applying the classical odd-/even-mode analysis method, the resonant characteristics of the new QMR have been analyzed. It shows that five modes can be excited, and two of them can be employed to form the lower passband, while the other three modes contribute to the higher passband. For verification, a dual-wideband BPF using the new QMR is designed, fabricated, and tested. Experimental results show that the CFs of the dual-wideband BPF centered at 2.96 GHz and 5.695 GHz with 3 dB fractional bandwidths of 27.7 and 23.4%, respectively. In addition, 20-dB suppression in upper-stopband ranges from 2.23 to 4.04f0, where f0 is the center frequency of the first passband. The measurement results are in good agreement with the prediction results.